ANALISIS INVESTASI INFRASTRUKTUR JALAN UNTUK MENDUKUNG PENGEMBANGAN KAWASAN PARIWISATA DI KABUPATEN BERAU - Rafli Yunianto Pratama; Tamam Rosid (JURNAL ILMIAH EDUNOMIKA, 2026)
Infrastructure investment plays a crucial role in regional tourism development, particularly in areas with significant natural and cultural potential. This study analyzes road infrastructure investment strategies to support tourism area development in Berau Regency, East Kalimantan, Indonesia. Employing a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), this research examines the relationships between infrastructure investment, accessibility improvement, tourism sector growth, and regional economic development. Primary data were collected from 215 respondents comprising government officials, tourism business operators, and local community members through structured questionnaires administered between January and March 2025. Secondary data included budget allocation documents, tourist arrival statistics, and road condition assessments from 2023-2025. The analysis reveals that road infrastructure investment significantly influences tourism accessibility (path coefficient 0.742, p<0.001), which subsequently affects tourist visit frequency (path coefficient 0.681, p<0.001) and regional economic performance (path coefficient 0.594, p<0.001). Budget allocation for road infrastructure in Berau Regency increased from IDR 127.3 billion in 2023 to IDR 185.6 billion in 2025, correlating with a 34.7% increase in tourist arrivals. The novelty of this research lies in integrating fiscal capacity analysis with tourism infrastructure planning through SEM-PLS methodology, providing empirical evidence for strategic budget allocation decisions. Findings indicate that prioritizing road connectivity to key tourism destinations such as Derawan Islands, Birang Waterfall, and Kelay River generates multiplier effects on local economic activities, employment creation, and community welfare improvement.